A COMPARATIVE CLINICAL STUDY TO ASSESS THE EFFICACY OF KARIMBIRUMBADI KASHAYAM AND VASAGULUCHYADI KASHAYAM IN PANDUROGA WITH SPECIAL REFERENCE TO IRON DEFICIENCY ANEMIA IN THE REPRODUCTIVE AGE GROUP OF WOMEN - Muhammed Nizamudheen C H; Soumya S B (International Journal of Ayurveda and Pharma Research, 2020)
This study is an attempt to clinically analyze the independent effect of Karimbirumbadi kashayam and Vasaguluchiadi kashayam in Panduroga and also compare their efficacy. Aims and Objectives: To evaluate the comparative efficacy of Karimbirumbadi kashayam and Vasaguluchyadi kashayam in Panduroga with special reference to iron deficiency anemia in the reproductive age group of women. Methodology: Among 46 registered subjects, 22 were registered in group A and 24were registered in group B. Out of which 20 subjects of A group and 20 subjects of B group completed the study. Group A was administered with 25ml of Karimbirumbadi kashayam with 40ml of luke warm water twice daily before food for 2 months and Group B was administered with 25ml of Vasaguluchyadi kashayam with 40ml of luke warm water and 10ml of Madhu as Anupana twice daily before food for 2 months. Objective and subjective parameters were analyzed using paired T test and Wilcoxon signed rank test respectively. Independent T test and Mann-Whitney U test were used to compare the parameters between the groups. Result: There was statistically significant improvement in the objective and subjective parameters (p<0.05 was observed). Conclusion: The study shows that both Karimbirumbadi kashayam and Vasaguluchyadi kashayam are effective in relieving the symptoms of Panduroga. Symptomatic relief was seen in both the group A & B, but there was no statistically significant difference between the groups in relieving these symptoms.